Assessment of the brain impact of soccer heading using pupillary light reflex - Nakao, Junzo; Muroi, Ai; Marushima, Aiki; Tasaki, Kuniharu; Inoue, Yoshiaki; Matsumaru, Yuji; Ishikawa, Eiichi (Frontiers in Neurology, 2025)
BackgroundSoccer heading is linked to adverse cognitive effects and changes similar to traumatic brain injury (TBI). In recent years, pupil light reflex (PLR) analysis via pupillometry offers a practical, reliable and objective neurological assessment for TBI. This is the first study to evaluate brain impact from soccer heading by evaluating PLR. We aimed to evaluate changes in PLR from heading and investigate if rubber balls reduce brain impacts compared with regular soccer balls.MethodsOur study involved 30 male healthy volunteer participants aged 18–29 years with >5 years of soccer experience. PLR was measured using the NPi-200 pupillometer system before and after performing every 10 headings, up to 30 headings with regular (session 1) and rubber soccer balls (session 2) in separate sessions. The parameters included neurological pupil index (NPi), constriction rate (CH), constriction velocity (CV), and maximum constriction velocity (MCV).ResultsIn session 1, CH and MCV significantly decreased compared with the baseline after 30 headings. In session 2, only CH significantly decreased compared with the baseline. CH significantly decreases from the 20th heading onwards in session 1 compared with session 2 (both at 20 and 30 headings; p < 0.001). CV significantly decreased after the 30th heading in session 1 compared with session 2 (p = 0.038). MCV significantly decreased at the 20th (p = 0.037) and 30th (p = 0.010) headings in session 1 compared with session 2.ConclusionHeading affects PLR, with regular soccer balls causing more significant changes than rubber balls. The use of rubber balls during training may mitigate brain impacts, offering a safer alternative for players.